INVESTIGATING THE APPLICATION OF NEXT-GENERATION SEQUENCING IN MOLECULAR DIAGNOSTICS: OPPORTUNITIES AND CHALLENGES - Majed Mohamed Hasan Abukaftah, Saad Bin Saeed Bin Abdullah Alqahtani, Yasmeen Mohammed Alreefi , Sami Abdullah Hadi Towhari , Mofareh Hussain Yahya Alabdaly , Salem Mikhdhar Almanjumi , Rashed Shaman R Aldhofiyan , Yahya Mohammed Ali Otayf , ,; Muteb Hasir Hassani , Naif Nahedh Rashad Al Harbi , Saeed Ali Yahia Hassany , Salem Mohammed Salem Sahhari, Abdulmohsen Abdulaziz Alsanawi , Bander Saleh Salem Albalaw , Abdulrahman Naif Alanazi, (Chelonian Research Foundation, 2022)
Molecular biology and clinical diagnostics have been transformed by next-generation sequencing (NGS) technologies, which allow for the quick and affordable study of genetic data. In this overview, we go through the development of NGS platforms and their uses in oncology and constitutional disorders, among other areas. With NGS, we can now identify new genes linked to disease and develop individualized treatment plans, which has greatly improved our understanding of genetic diseases. NGS is essential to oncology because it helps to predict treatment outcomes, characterize genetic changes in cancer, and guide therapeutic choices. NGS has the potential to change clinical practice, but obstacles including complicated data analysis and payment problems prevent it from being widely used. However, there is hope that future developments in NGS technology and legal frameworks will help to overcome these obstacles and further incorporate NGS into standard patient treatment. All things considered, NGS is a paradigm shift in genomic analysis that is propelling precision medicine forward and changing the way that genetic illnesses and cancer are diagnosed and treated. Key words: Next-generation sequencing, NGS, molecular diagnostics, constitutional disorders, oncology, precision medicine, genetic diseases, cancer genomics, personalized medicine, clinical applications.